ANALISIS KINERJA KEUANGAN DENGAN MENGUKUR TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RISK PROFILE, GOOD GOVERNANCE, EARNINGS, AND CAPITAL (RGEC) (STUDI KASUS PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK) - Putri, Vanessa; Maharani, Yunita; Mulyani, Hendarti Tri Setyo (STIE IBEK Pangkalpinang, 2023)
This study aims to analyze the financial performance of PT Bank Tabungan Negara (Persero) Tbk by measuring the health level of banks using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) in accordance with Bank Indonesia Regulation No. 13/PBI/2011. This type of research is quantitative research and uses secondary data sources in the form of annual reports from PT Bank Tabungan Negara (Persero) Tbk for 5 years, from 2018 to 2022 downloaded from the Bank BTN website. The analysis technique used in this research is descriptive with the method of risk profile, good corporate governance, profitability and capital (RGEC). The results of this study are expected to contribute more comprehensively in weighing and making the right management decisions for PT Bank Tabungan Negara (Persero) Tbk in the future from seeing how their financial performance and bank health over the past 5 years. The results showed that PT Bank Tabungan Negara (Persero) Tbk for the period 2018-2022 was ranked second with a healthy predicate, which shows that the financial performance of PT Bank Tabungan Negara (Persero) Tbk over the past 5 years has been good and Bank BTN is considered capable of dealing with significant negative influences from changes in business conditions and other external factors.